Optimal. Leaf size=28 \[ 3+e^{-3+3 \left (1+e^{\frac {x^2}{x+x^2}}\right )-x} x \]
________________________________________________________________________________________
Rubi [F] time = 3.30, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{3 e^{\frac {x}{1+x}}-x} \left (1+x+3 e^{\frac {x}{1+x}} x-x^2-x^3\right )}{1+2 x+x^2} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{3 e^{\frac {x}{1+x}}-x} \left (1+x+3 e^{\frac {x}{1+x}} x-x^2-x^3\right )}{(1+x)^2} \, dx\\ &=\int \left (\frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2}+\frac {e^{3 e^{\frac {x}{1+x}}-x} x}{(1+x)^2}+\frac {3 e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}} x}{(1+x)^2}-\frac {e^{3 e^{\frac {x}{1+x}}-x} x^2}{(1+x)^2}-\frac {e^{3 e^{\frac {x}{1+x}}-x} x^3}{(1+x)^2}\right ) \, dx\\ &=3 \int \frac {e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}} x}{(1+x)^2} \, dx+\int \frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2} \, dx+\int \frac {e^{3 e^{\frac {x}{1+x}}-x} x}{(1+x)^2} \, dx-\int \frac {e^{3 e^{\frac {x}{1+x}}-x} x^2}{(1+x)^2} \, dx-\int \frac {e^{3 e^{\frac {x}{1+x}}-x} x^3}{(1+x)^2} \, dx\\ &=3 \int \left (-\frac {e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}}}{(1+x)^2}+\frac {e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}}}{1+x}\right ) \, dx+\int \frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2} \, dx-\int \left (e^{3 e^{\frac {x}{1+x}}-x}+\frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2}-\frac {2 e^{3 e^{\frac {x}{1+x}}-x}}{1+x}\right ) \, dx+\int \left (-\frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2}+\frac {e^{3 e^{\frac {x}{1+x}}-x}}{1+x}\right ) \, dx-\int \left (-2 e^{3 e^{\frac {x}{1+x}}-x}+e^{3 e^{\frac {x}{1+x}}-x} x-\frac {e^{3 e^{\frac {x}{1+x}}-x}}{(1+x)^2}+\frac {3 e^{3 e^{\frac {x}{1+x}}-x}}{1+x}\right ) \, dx\\ &=2 \int e^{3 e^{\frac {x}{1+x}}-x} \, dx+2 \int \frac {e^{3 e^{\frac {x}{1+x}}-x}}{1+x} \, dx-3 \int \frac {e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}}}{(1+x)^2} \, dx-3 \int \frac {e^{3 e^{\frac {x}{1+x}}-x}}{1+x} \, dx+3 \int \frac {e^{3 e^{\frac {x}{1+x}}-x+\frac {x}{1+x}}}{1+x} \, dx-\int e^{3 e^{\frac {x}{1+x}}-x} \, dx-\int e^{3 e^{\frac {x}{1+x}}-x} x \, dx+\int \frac {e^{3 e^{\frac {x}{1+x}}-x}}{1+x} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.64, size = 21, normalized size = 0.75 \begin {gather*} e^{3 e^{1-\frac {1}{1+x}}-x} x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.79, size = 17, normalized size = 0.61 \begin {gather*} x e^{\left (-x + 3 \, e^{\left (\frac {x}{x + 1}\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.21, size = 44, normalized size = 1.57 \begin {gather*} x e^{\left (-\frac {x^{2} - 3 \, x e^{\left (\frac {x}{x + 1}\right )} - 3 \, e^{\left (\frac {x}{x + 1}\right )}}{x + 1} - \frac {x}{x + 1}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.32, size = 18, normalized size = 0.64
method | result | size |
risch | \(x \,{\mathrm e}^{3 \,{\mathrm e}^{\frac {x}{x +1}}-x}\) | \(18\) |
norman | \(\frac {\left (x^{2}+x \right ) {\mathrm e}^{3 \,{\mathrm e}^{\frac {x}{x +1}}-x}}{x +1}\) | \(27\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.45, size = 19, normalized size = 0.68 \begin {gather*} x e^{\left (-x + 3 \, e^{\left (-\frac {1}{x + 1} + 1\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 1.26, size = 17, normalized size = 0.61 \begin {gather*} x\,{\mathrm {e}}^{3\,{\mathrm {e}}^{\frac {x}{x+1}}}\,{\mathrm {e}}^{-x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 6.85, size = 12, normalized size = 0.43 \begin {gather*} x e^{- x + 3 e^{\frac {x}{x + 1}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________